2014
DOI: 10.1002/chem.201404705
|View full text |Cite
|
Sign up to set email alerts
|

[(IPent)PdCl2(morpholine)]: A Readily Activated Precatalyst for Room‐Temperature, Additive‐Free Carbon–Sulfur Coupling

Abstract: A series of new, easily activated NHC-Pd(II) precatalysts featuring a trans-oriented morpholine ligand were prepared and evaluated for activity in carbon-sulfur cross-coupling chemistry. [(IPent)PdCl2(morpholine)] (IPent=1,3-bis(2,6-di(3-pentyl)phenyl)imidazol-2-ylidene) was identified as the most active precatalyst and was shown to effectively couple a wide variety of deactivated aryl halides with both aryl and alkyl thiols at or near ambient temperature, without the need for additives, external activators, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 77 publications
3
41
0
Order By: Relevance
“…Recent work from the groups of Nolan and Organ has demonstrated that the PEPPSI scaffold can accommodate bulky ligands, such as IPr* (REF. 49), IPent (REFS 5052), IPent Cl (REFS 5356) and IHept Cl (REFS 57,58), without any need to modify the precatalyst structure. Use of the PEPPSI framework with these newly designed NHC ligands has led to increased reactivity for the arylation of amines (using IPr* (REF.…”
Section: Pd-based Precatalyst Development Since 2012mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work from the groups of Nolan and Organ has demonstrated that the PEPPSI scaffold can accommodate bulky ligands, such as IPr* (REF. 49), IPent (REFS 5052), IPent Cl (REFS 5356) and IHept Cl (REFS 57,58), without any need to modify the precatalyst structure. Use of the PEPPSI framework with these newly designed NHC ligands has led to increased reactivity for the arylation of amines (using IPr* (REF.…”
Section: Pd-based Precatalyst Development Since 2012mentioning
confidence: 99%
“…Additionally, by further understanding the activation mechanism, it has been shown that replacing the pyridine motif with morpholine allows for the room temperature coupling of thiols and aryl chlorides using IPent (REF. 52). …”
Section: Pd-based Precatalyst Development Since 2012mentioning
confidence: 99%
“…Other base/solvent combinations such as NaO t Bu/toluene and KO t Bu/DME did not work, affording 0% conversion (entries 2 and 11), and secondary alcoholic solvents, such as IPA, afforded less than 50% conversion (entries 13 and 14). Hence, the phenylboronic acid was changed to 2,6-xyleneboronic acid to examine the activities of other complexes for a prolonged reaction time of 7 h. The results are collected in Table 1 (entries [15][16][17][18][19][20][21][22]. Hence, the phenylboronic acid was changed to 2,6-xyleneboronic acid to examine the activities of other complexes for a prolonged reaction time of 7 h. The results are collected in Table 1 (entries [15][16][17][18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…When obtaining the optimum conditions to screen the family of complexes 1-6, the temperature was raised to 50°C, and the six complexes showed close activities to afford more than 80% conversion within 1 h with the same starting materials, only complexes 4 and 6 showing inferior conversion (for 4: 71%; for 6: 43%). Based on the same conditions, 7 achieved 5% yield, 8 54%, 9 43% and 10 39% (entries [19][20][21][22]. Comparing the activities of the family of complexes, only complex 1 allowed the coupling to proceed in high yield (75%; entry 16).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that under the given conditions benzimidazolium salts 4a-4d and 5a-5d are unsuitable as N-heterocyclic carbene ligands in Pdcatalyzed Suzuki reaction (the yields of 4-methylbiphenyl were 12-30%). In keeping with the latest views on the mechanism of catalysis of the Suzuki reaction by palladium complexes with N-heterocyclic carbenes, the carbene residue remains firmly linked to the metal at all steps of the catalytic cycle [6]. The low yield of the cross-coupling product may be accounted for by inhibitory effect of the bulky, fairly rigid, and hydrophobic triterpene residue on the formation of carbenemetal bond.…”
mentioning
confidence: 80%